ZINC40099027 activates human focal adhesion kinase by accelerating the enzymatic activity of the FAK kinase domain - Rashmi; Shyam K. More; Qinggang Wang; Emilie E. Vomhof‐DeKrey; James E. Porter; Marc D. Basson (Wiley, 2021)
Abstract Focal adhesion kinase (FAK) regulates gastrointestinal epithelial restitution and healing. ZINC40099027 (Zn27) activates cellular FAK and promotes intestinal epithelial wound closure in vitro and in mice. However, whether Zn27 activates FAK directly or indirectly remains unknown. We evaluated Zn27 potential modulation of the key phosphatases, PTP‐PEST, PTP1B, and SHP2, that inactivate FAK, and performed in vitro kinase assays with purified FAK to assess direct Zn27‐FAK interaction. In human Caco‐2 cells, Zn27‐stimulated FAK‐Tyr‐397 phosphorylation despite PTP‐PEST inhibition and did not affect PTP1B‐FAK interaction or SHP2 activity. Conversely, in vitro kinase assays demonstrated that Zn27 directly activates both full‐length 125 kDa FAK and its 35 kDa kinase domain. The ATP‐competitive FAK inhibitor PF573228 reduced basal and ZN27‐stimulated FAK phosphorylation in Caco‐2 cells, but Zn27 increased FAK phosphorylation even in cells treated with PF573228. Increasing PF573228 concentrations completely prevented activation of 35 kDa FAK in vitro by a normally effective Zn27 concentration. Conversely, increasing Zn27 concentrations dose‐dependently activated kinase activity and overcame PF573228 inhibition of FAK, suggesting the direct interactions of Zn27 with FAK may be competitive. Zn27 increased the maximal activity (Vmax) of FAK. The apparent Km of the substrate also increased under laboratory conditions less relevant to intracellular ATP concentrations. These results suggest that Zn27 is highly potent and enhances FAK activity via allosteric interaction with the FAK kinase domain to increase the Vmax of FAK for ATP. Understanding Zn27 enhancement of FAK activity will be important to redesign and develop a clinical drug that can promote mucosal wound healing.